Fisher Effect in Post-Unification Germany - Insights for Firms, Central Banks and Governments - Cordelia Friesendorf; S. Raja Sethu Durai (Research Journal for Applied Management (RJAM), 2021)
Irving Fisher's (1930) hypothesis is a pillar in international economic theory used by Central banks and financial ministries to assess the impact of real and nominal variables that are essential for firm-level growth. This paper examines the validity of generalized Fisher's hypothesis for post-unification Germany for the time-period beginning January 1991 until March 2020 through a frequency-time domain framework using continuous wavelet analysis. We make two inferences from the empirical analysis; first, the generalized Fisher hypothesis holds perfectly well for the study period. Second, the relationship between real stock return and inflation exhibited in the post-financial crisis period is attributed to the indirect growth effects of the Germany's overall domestic product. The results provide valuable insights for firms, banks and governments.
Keywords: E43; E44; 650; Fisher hypothesis; real stock return; inflation; wavelet analysis; post-unification